The recovery of used palm cooking oil using bagasse as adsorbent - Mariam Firdhaus Mad Nordin; Marinah Muhammad; Rizki Wannahari (2011)
The use and reduce cooking oil is a common phenomena in our society. While some of this cooking oil is further refine most of it however and not subject to any filtration in the refining process medium such as carbon active, silica are commonly use. However the used of bagasse as adsorbent is not common. This is odd especially when structural component of bagasse which is made up of carbon material is suitable as adsorbent and the fact that, adsorbent bagasse further reduce solid waste disposal and hence reducing one source of environmental pollution.This study was undertaken to explore the possibility of using bagasse as adsorbent. Specifically, bagasse is being experimented to reduce the harmful content such as Free Fatty Acid (FFA) and color density in used cooking oil. The variation of adsorbent weight and contact time are used in this research as parameters to determine the effective time and the amount of adsorbent that should be used in the oil refining process. From the experiment conducted, it can be established that bagasse when use as an adsorbent can reduce FFA to 82.14% which is lower the harmful limit.This result is obtained when using 7.5 gr of bagasse for 60 m contact time. Similarly, the color of oil is reduced to 75.67% which is significant and this is base on 10 gr of bagasse with 60 m of contact time